Susan W. Woolley, Lee Airton (eds.). Teaching about Gender Diversity. Teacher-Tested Lesson Plans for K-12 classrooms. Toronto 2020: Canadian Scholars. Pp. 334. - Adamczewski, Jakub (Journal of Gender and Power, 2021)
Book-Review